1994
DOI: 10.1002/asna.2103150508
|View full text |Cite
|
Sign up to set email alerts
|

Non‐rigid rotation of solar spicules

Abstract: Ha profiles of chromospheric spicules computed for a variety of rotational behavior are compared with an observed profile, which was derived by averaging 11 H a profiles taken near times of maximum spicule intensity. If turbulent velocity is small or equals zero, calculated profiles are in good agreement with the observed one under the conditions that rotation is non-rigid (faster rotation further away from the axis of the spicule) and the source function decreases in the direction from the spicule axis to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It must be mentioned here, that some observations show the tilt of spicule spectra relative to the direction of dispersion, which was explained as due to the rotation of spicules around their axes (Pasachoff et al (1968); Rompolt (1975); Pishkalo (1994)).…”
Section: Life Time and Motionsmentioning
confidence: 91%
See 1 more Smart Citation
“…It must be mentioned here, that some observations show the tilt of spicule spectra relative to the direction of dispersion, which was explained as due to the rotation of spicules around their axes (Pasachoff et al (1968); Rompolt (1975); Pishkalo (1994)).…”
Section: Life Time and Motionsmentioning
confidence: 91%
“…These periodic perturbations are the subject of our discussion in the remaining part of the paper. It must be mentioned here, that some observations show the tilt of spicule spectra relative to the direction of dispersion, which was explained as due to the rotation of spicules around their axes (Pasachoff et al (1968); Rompolt (1975); Pishkalo (1994)). In this regards, it is interesting to note the recent SOHO/CDS observations, which also suggest the rotation in macro-spicules, interpreted as a sort of giant solar tornado (Pike and Mason (1998)).…”
Section: Life Time and Motionsmentioning
confidence: 92%
“…Examples include siphon flows in coronal loops (Orlando et al 1995a(Orlando et al , 1995b, counterstreaming (Lin et al 2003), and field-aligned flows within filament channels (Lin et al 2005), spicules (Hollweg et al 1982;De Pontieu et al 2004;Zaqarashvili & Erdélyi 2009;Scullion et al 2011), Evershed flows within sunspots (Montesinos & Thomas 1997;Plaza et al 1997). In addition, non-thermal broadenings have been observed within the chromosphere (Beckers 1968(Beckers , 1972Pishkalo 1994;Jess et al 2009Jess et al , 2015. These non-thermal broadenings are usually interpreted as Alfvén waves and have been considered as a possible mechanism responsible for Type-I spicule formation (Hollweg et al 1982;Sterling & Hollweg 1988;Hollweg 1992;Kudoh & Shibata 1999;James et al 2003; though it is possible that other mechanisms such as leakage of p-mode oscillations along inclined field lines are responsible (De Pontieu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pishkalo (1994) found that about half of all spicules showed spectral tilts at some point in their lifetimes and that rotation must be in the range of 20−35 km s −1 to fit the observed spectral profiles.…”
Section: Introductionmentioning
confidence: 99%